2007
DOI: 10.1262/jrd.18063
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Growth Performances of Offspring Produced by a Pair of Cloned Cattle and Their Nuclear Donor Animals

Abstract: Abstract. In the present study, the growth performance of a calf produced by mating a somatic cell cloned dam and sire was compared with that of its full siblings produced by mating the cattle used as nuclear donors for the cloned animals. The somatic cell cloned dam and sire were derived from cultured cumulus cells and ear cells, respectively. The cloned dam was artificially inseminated with semen from the cloned sire. A female calf was produced that was reared under general group feeding conditions. The calf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
1
19
0
3
Order By: Relevance
“…These empirical facts can be explained using a mouse model system; it is assumed that there is no risk increase in terms of inducement of abnormalities due to epigenetic errors in the progeny of cloned animals, since any epigenetic errors existing in a clone's genome would be erased during the process of gamete genesis and fertilization [25]. It should be noted that other empirical evidence collected by observation of progeny, such as the calf production rate with artificial insemination, gestation period, birth weight, growth performance, blood parameters and production performance, are also consistent with this assumption [2,5,26] Therefore, this evidence strongly suggests that the progeny of SCNT cattle can be produced for consumption in a manner similar to conventionally bred cattle.…”
Section: Discussionmentioning
confidence: 57%
“…These empirical facts can be explained using a mouse model system; it is assumed that there is no risk increase in terms of inducement of abnormalities due to epigenetic errors in the progeny of cloned animals, since any epigenetic errors existing in a clone's genome would be erased during the process of gamete genesis and fertilization [25]. It should be noted that other empirical evidence collected by observation of progeny, such as the calf production rate with artificial insemination, gestation period, birth weight, growth performance, blood parameters and production performance, are also consistent with this assumption [2,5,26] Therefore, this evidence strongly suggests that the progeny of SCNT cattle can be produced for consumption in a manner similar to conventionally bred cattle.…”
Section: Discussionmentioning
confidence: 57%
“…Their offspring were healthy, and the telomere lengths in their leukocytes were normal [16]. In the second, we showed that artificial insemination of a healthy cloned cow with normal-length telomeres using spermatozoa from another healthy cloned bull yielded healthy offspring with normal telomere lengths [29]. Our series of studies provides compelling evidence that, during gametogenesis in the cloned cattle, telomerase activity in the germ line restores the short telomeres derived from the donor somatic cell to a telomere length typical of the gametes of normal cattle, even if the somatic cells of cloned animals have short telomeres (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…It should be noted that similarities have been reported for the growth curves of such things as body weight and withers height among nuclear donor and clones originating from the same nuclear donor [6, 13, 26, 31, 33-35, 37, 39]. Similarities in growth curve have also been reported among offspring produced by a pair of cloned cattle and their nuclear donor animals [45].…”
Section: Growth Performancementioning
confidence: 83%
“…Fifty-nine somatic cell cloned cattle (Table 7) and 5 offspring ( Table 8) were employed in this category [6,7,9,10,12,13,17,18,21,23,26,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The observation period covered the stages from Developmental Node 2 (perinatal period) to Developmental Node 5 (post-puberty maturation and aging).…”
Section: Growth Performancementioning
confidence: 99%